Analysis of patient care cost for selected preventable diseases in Intensive Care Unit at Lady Ridgway Hospital in 1992. - Jayatissa, K.L.R (My University, 1992)
The study revealed that the Ministry of health has achieved a certain level of success in controlling the preventable diseases. Intensive care utilization for this categories was only 23 per cent as compared to 77 per cent for non preventable diseases. Per patient day cost at the ICU was Rs.3,306.00.Which is almost ten times greater than that for general ward treatment at LRH. The mortality rate for patients with preventable diseases had remained at a high level (60 per cent) 70 per cent of the preventable conditions were due to birth asphyxia and complications of LBW. These two conditions produce high incidence of admissions under one month (97 per cent out of all neonates).Among the non preventable diseases, there were patients with long standing public health problems such as complications of worm infestation(0.7 per cent), gastroenteritis(4.1 per cent), malaria(0.7 per cent), neonatal tetanus(1.4 per cent), tetanus(1.4 per cent).tuberculosis(1.4 per cent) and typhoid (0.7 per cent).There were also patients appearing with newly highlighted public health problems such as dengue hemorrhagic fever(2.1 per cent) and encephalitis(7.5 per cent) which could be a major public health problems in the future.8.9 per cent of patients presented as poisoning which is easily preventable.55 per cent of the total ICU cost for preventable diseases has consumed by non survivors as compared to the cost consumed by survivors. This highlights well known important concept of prevention is better than cure. There is a growing demand for intensive care by the health professionals and other pressure groups, this may not be a right investment considering the loss of opportunity of primary and secondary care for large numbers due to lack of resources. While accepting the fact, that intensive care are integral part of tertiary care, these should not be established at the expense of basic primary care